Physical map of the genome of the green phototrophic bacterium Chlorobium tepidum. - Naterstad, K (1995)
A physical restriction map of the chromosome of the green sulfur bacterium Chlorobium tepidum was generated by determining the order of the fragments obtained after digestion with the restriction endonucleases XbaI and PacI and subsequent separation of the fragments by pulsed-field gel electrophoresis. The size of the chromosome is estimated to be 2.1 Mb. Fifteen genes and operons, mainly encoding proteins involved in photosynthesis, have been placed on this map by hybridization to fragments obtained after single- and double-restriction digestions.